Quantitative Content Parameter in the Standardization of Veratrum Aqua, Veratrum Lobelianum Bernh. Based Drug - E. V. Melnik; M. V. Belova; I. A. Tyurin; G. V. Ramenskaya (Разработка и регистрация лекарственных средств)
Introduction. According to the XIV Edition of the Russian Federation State Pharmacopoeia, the quality control of the «Veratrum Lobelianum rhizome and roots» herbal substance is carried out through the determination of the alkaloid sum by means of the titration-based method. There are no selective and sensitive instrumental methods for the quantitative analysis of veratrum aqua active ingredients either. Veratrum aqua is produced from the mentioned above herbal substance. Therefore, the study of veratrum aqua alkaloid composition is relevant, as well as the development of a modern analytical method for individual alkaloid determination that can be implemented in veratrum aqua standardization.Aim. To develop an approach to the quantitative analysis in Veratrum Aqua standardization.Materials and methods. Two analytical methods were developed: one for the veratrum alkaloid determination in veratrum aqua samples by means of high performance liquid chromatography coupled with tandem mass-spectrometry (HPLC-MS/MS), another – for jervine, the main veratrum aqua alkaloid, quantitation by means of HPLC with diode-array detector (HPLC-DAD).Results and discussion. Three main alkaloids, namely jervine, protoveratrine A and protoveratrine B, were identified in veratrum aqua. Jervine was found to be the most abundant one, hence it was chosen for the further development of a more affordable HPLC-DAD method. This method was validated for specificity, linearity, accuracy and precision. Jervine concentrations were measured in seven veratrum aqua samples produced by different manufacturers.Conclusion. The highest jervine concentration among the examined samples was found to be 170 µg/ml, the lowest – 136 µg/ml. It is proposed to implement the following quantitative content parameter in veratrum aqua standardization: «Quantitative test. Jervine content should be not lessthan 136 µg/ml». This parameter is to be determined by HPLC-DAD.